Randomised controlled trial of clinical medication review by a pharmacist of elderly patients receiving repeat prescriptions in general practice - Zermansky, Arnold G; Petty, Duncan R; Raynor, David K; Freemantle, Nick; Vail, Andy; Lowe, Catherine J (BMJ, 2001)
Abstract Objective: To determine whether a pharmacist can effectively review repeat prescriptions through consultations with elderly patients in general practice. Design: Randomised controlled trial of clinical medication review by a pharmacist against normal general practice review. Setting: Four general practices. Participants: 1188 patients aged 65 or over who were receiving at least one repeat prescription and living in the community. Intervention: Patients were invited to a consultation at which the pharmacist reviewed their medical conditions and current treatment. Main outcome measures: Number of changes to repeat prescriptions over one year, drug costs, and use of healthcare services. Results: 590 (97%) patients in the intervention group were reviewed compared with 233 (44%) in the control group. Patients seen by the pharmacist were more likely to have changes made to their repeat prescriptions (mean number of changes per patient 2.2 v 1.9; difference=0.31, 95% confidence interval 0.06 to 0.57; P=0.02). Monthly drug costs rose in both groups over the year, but the rise was less in the intervention group (mean difference £4.72 per 28 days, −£7.04 to -£2.41); equivalent to £61 per patient a year. Intervention patients had a smaller rise in the number of drugs prescribed (0.2 v 0.4; mean difference −0.2, −0.4 to −0.1). There was no evidence that review of treatment by the pharmacist affected practice consultation rates, outpatient consultations, hospital admissions, or death rate. Conclusions: A clinical pharmacist can conduct effective consultations with elderly patients in general practice to review their drugs. Such review results in significant changes in patients' drugs and saves more than the cost of the intervention without affecting the workload of general practitioners. What is already known on this topic Review of patients on long term drug treatment is important but is done inadequately Evidence from the United States shows that pharmacists can improve patient care by reviewing drug treatment What this study adds Consultations with a clinical pharmacist are an effective method of reviewing the drug treatment of older patients Review by a pharmacist results in more drug changes and lower prescribing costs than normal care plus a much higher review rate Use of healthcare services by patients is not increased